2019
DOI: 10.1111/anae.14776
|View full text |Cite
|
Sign up to set email alerts
|

Development of evidence‐based recommendations for procedure‐specific pain management: PROSPECT methodology

Abstract: Summary Effective peri‐operative pain management is a prerequisite for optimal recovery after surgery. Despite published evidence‐based guidelines from several professional groups, postoperative pain management remains inadequate. The procedure‐specific pain management (PROSPECT) collaboration consists of anaesthetists and surgeons with broad international representation that provide healthcare professionals with practical and evidence‐based recommendations formulated in a way that facilitates clinical decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
195
0
35

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(233 citation statements)
references
References 30 publications
3
195
0
35
Order By: Relevance
“…The methods of this review adhered to the PROSPECT methodology as previously reported . Specific to this study, the EMBASE, MEDLINE, PubMed and Cochrane Databases (Cochrane Central Register of Controlled Trials, Cochrane Database of Abstracts or Reviews of Effects, Cochrane Database of Systematic Reviews) were searched for RCTs published between 31 May 2006 and 15 October 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of this review adhered to the PROSPECT methodology as previously reported . Specific to this study, the EMBASE, MEDLINE, PubMed and Cochrane Databases (Cochrane Central Register of Controlled Trials, Cochrane Database of Abstracts or Reviews of Effects, Cochrane Database of Systematic Reviews) were searched for RCTs published between 31 May 2006 and 15 October 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Quality assessment, data extraction and data analysis adhered to the PROSPECT methodology . Studies that reported pooled data from patients undergoing mixed procedures of cancer and non‐cancer breast surgery were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The methods of this review adhered to PROSPECT methodology as previously reported . Specific to this study, the Embase, MEDLINE, PubMed and Cochrane Databases (Cochrane Central Register of Controlled Trials, Cochrane Database of Abstracts or Reviews of Effects, Cochrane Database of Systematic Reviews) were searched for RCTs published between 1 January 2006 and 15 April 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Quality assessment, data extraction and data analysis adhered to PROSPECT methodology . Pain intensity scores were used as the primary outcome measure.…”
Section: Methodsmentioning
confidence: 99%
“…The PECS‐2 or serratus plane block may provide analgesia for breast surgical procedures including axillary dissection, depending on the spread of the solution, but these blocks have never been properly studied in randomised controlled trials comparing them with standard analgesia, and consequently the PROSPECT methodology prevents us from recommending them at this time. We refer to our methodology paper published last year [3] and our website (http://www.postoppain.org) .…”
mentioning
confidence: 99%